Potensi Desa Wisata sebagai Alternatif Destinasi Wisata New Normal - Syaiful Ade Septemuryantoro (Media Wisata, 2021)
Tourism villages are projected as an alternative to the new normal era tourist destinations. The tourism segment changes along with the new normal era, so tourists will choose private destinations such as nature-based tourism. The existence of a tourist village that implements CHSE (Cleanliness, Health, Safety and Environment Sustainability) assures tourists to travel safely in tourist villages. The research method uses descriptive qualitative analysis with a case study approach. The SWOT analysis shows that the potential of a tourist village can be developed into a developed tourism village, currently, there are 16 certified tourist villages and other tourist villages